2020
DOI: 10.3389/fphar.2020.00248
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Clinical Drugs as AdoMetDC Inhibitors Using the SCAR Strategy

Abstract: With the escalating costs in drug development, discovering new uses of approved drugs, i.e., drug repurposing, has attracted increasing interest. Spermidine and spermine are important polyamines for most cells and their biosynthesis are strictly regulated by the polyamine metabolic network. In cancerous cells and tumor environments, the concentrations of polyamines are much higher than in normal cells. During the synthesis of spermidine and spermine, an amino-propyl group is provided by decarboxylated S-adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…2 Therefore, it is of great value to find inhibitors that can inhibit the polyamine levels. 20,36,37 In this work, we used ODC as an example to assess the value of targeting ISPs with multipurpose ligands. ODC is an ISP in the polyamine metabolic network, and it is the rate-limiting enzyme in polyamine synthesis and regulated by both homodimerization and the binding of OAZ1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Therefore, it is of great value to find inhibitors that can inhibit the polyamine levels. 20,36,37 In this work, we used ODC as an example to assess the value of targeting ISPs with multipurpose ligands. ODC is an ISP in the polyamine metabolic network, and it is the rate-limiting enzyme in polyamine synthesis and regulated by both homodimerization and the binding of OAZ1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies confirmed that polyamine contents are significantly elevated in many cancers 2 . Therefore, it is of great value to find inhibitors that can inhibit the polyamine levels 20,36,37 . In this work, we used ODC as an example to assess the value of targeting ISPs with multipurpose ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as the other similar proteases [33] , targeting these priming proteases might be an effective choice to disrupt the infection of this virus. Based on our recent work [17] , [19] , [20] , we adopted the SCARdock protocol to repurpose clinic drugs as potential inhibitors of these priming proteases in this study. We identified several clinic drugs that might be useful as the covalent inhibitors of CatB, CatL, and TMPRSS2.…”
Section: Discussionmentioning
confidence: 99%
“…To help the discovery of covalent drugs, we previously established a “steric-clashes alleviating receptor (SCAR)” strategy [17] for the in silico docking and screening of covalent drugs enlightened by in silico protein design [18] . More recently, we demonstrated that our SCARdock method is also useful in drug repurposing [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Realizing the potential use of SCAR in discovering both covalent and non-covalent inhibitors, we recently demonstrated that SCAR is also quite efficient in drug repurposing (Y. Zhang et al, 2020). Compared with non-covalent drugs, covalent drugs have the following advantages (Mah et al, 2014): (i) covalent drugs have better biochemical efficiency since they are more competitive than many non-covalent endogenous substrates and cofactors; (ii) covalent drugs cause lower patient burden and delay the emergence of drug resistance due to lower and less frequent dosing; (iii) covalent drugs might have better target specificity by reacting with a non-conserved nucleophilic amino acid with careful designs (Cuesta et al, 2020).…”
Section: Introductionmentioning
confidence: 99%